Discutindo botânica com alunos de Ensino Médio a partir de metodologias ativas - FONSECA, Mara Souza Dos Santos (2024)
Plant Biology is a fascinating field of study, research and practical applications in which plant morphology and anatomy are found, essential for the scientific knowledge of plants. The neglect and lack of interest in the structures that make up the body of plants are due to the lack of knowledge of the value of the interaction they have with other living beings, with the need to include studies of the function of these organisms with interdisciplinary tools in clear and didactic ways along with other sciences. Aiming to sensitize high school students to the importance of studying botany, awakening the critical view of those involved, considering their life stories and knowledge acquired to discuss the science of plants, an eco-pedagogical workshop was held with classes on plant morphology and chemistry for the observation of the development of the plant body in a classroom at the State School of Elementary and Secondary Education Profa. Argentina Pereira, Riozinho/Bragança/ Pará in two classes of first-year high school students, with thirty students each, between fifteen and seventeen years old, during five meetings of two hours/class each, between the months of October and November 2022, using as an active teaching-learning methodology the study of the germination specie of the black bean seed Phaseolus lunatus Lineu (Fabaceae) to observe the development of the initial structures of the plant's body. The students were distributed into teams of three people, where each team received a disposable cup with toilet paper moistened with water, to be used as a substrate and three black split bean seeds, to take care of, monitor, record, discuss and draw the events of the germination. The content analysis of the present study consisted of exploring the material, processing the results and interpreting the data collected from conversation circles, reports, drawings, notes and field diary. The results revealed the students' involvement in the scientific method, based on observation and construction of hypotheses. The active methodology achieved its objective and sensitized students to a more affective look at botanical sciences. With the guidance of the educators, the results were considered satisfactory, as the students actively participated in classes, interacted and shared information with the teachers on the proposed theme, contributing to the development of more critical, reflective, collaborative professionals with the ability to apply content learned in different disciplines.